Meningkatkan Keterampilan Proses Sains Siswa Melalui Penggunaan Modul Fisika Berbasis Inkuiri Terbimbing - Ana Della; Tri Ariani; Endang Lovisa (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
This study aimed to analyze the improvement of students' science process skills through the use of a Guided Inquiry-based physics module on the topic of Light and Optical Instruments. The research employed a quasi-experimental method with a One-Group Pre-test Post-test Design. The participants consisted of 30 students from Class VIII.1 of SMP Negeri 14 Lubuklinggau. Data were collected through pre-test and post-test on science process skills and analyzed using descriptive statistics, percentages, and Normalized Gain (N-Gain). The results showed that the students' average score increased from 29.33 in the pre-test to 75.00 in the post-test, with an N-Gain score of 0.65, which is classified as a moderate improvement. In addition, all indicators of science process skills showed improvement after the learning process. These findings indicate that the Guided Inquiry-based physics module is effective in improving students' science process skills and can be used as an alternative teaching material in physics learning.